Web-based engineering education : critical design and effective tools - Russell, Donna, 1955-; Haghi, A. K. (Hershey, PA : Engineering Science Reference, 2010)
'This book evaluates the usefulness of advanced learning systems in delivering instructions in a virtual academic environment for different engineering sectors. The learning process discussed in each chapter will include a walk-through of a case problem-solving exercise in the virtual company environment'--Provided by publisher.
Includes bibliographical references (p. 207-223) and index.
Keywords: Engineering -- Study and teaching (Higher); Web-based instruction; Educational Web sites; Distance education; Engineers -- In-service training